Technological Cooperation Networks at Bio-Manguinhos: the Role of Information and Communication Technologies - Lázaro Pereira de Oliveira; Claudio Pitassi; Antônio Augusto Gonçalves (BBR: Brazilian Business Review)
This article identifies and discusses the contribution of information and communication technologies (ICTs) to the technological cooperation projects of Bio-Manguinhos, a pharmaceutical manufacturer that belongs to Osvaldo Cruz Foundation (FIOCRUZ), responsible for producing vaccines, reagents and biopharmaceuticals, with priority on meeting the needs of the Brazilian public health system. It is a case study with a qualitative approach for descriptive and explanatory purposes. The data were collected from 14 interviews conducted with managers of research and development (R&D) projects with high relevance to the organization. The results allow concluding that the ICTs requiring greater interdependence between partners and two-way knowledge flows have not yet been used. They also show the importance of closer cooperation between the information technology (IT) and R&D areas. A future positioning of Bio-Manguinhos as a technological center focused on discovery and sale of new active ingredients can favor the use of tools that promote greater integration between the partners of technology cooperation networks.